Baking and cookie quality of mixtures of whole amaranth flour and refined wheat flour - Espitia-Rangel, Eduardo; Martínez-Cruz, Eliel; Lozano-Grande, Azalia; René Hortelano Santa Rosa; Valverde-Ramos, Miriam; Sesma-Hernández, Fernanda (Revista Mexicana de Ciencias Agrícolas, 2022)
The imbalance between excessive intake and energy expenditure due to the consumption of refined carbohydrates and fats can be associated with overweight and obesity, causing a public health problem as currently happens in Mexico. Refined flour of bread wheat in the form of sweet bread and cookies are part of this intake. An alternative to this problem is the substitution in the making of these products for flour of whole grains, such as amaranth, for which the dough, as well as its baking and cookie quality must be characterized. Therefore, the objective of the present research was to evaluate the rheological characteristics of the dough, volume of bread and cookie factor of mixtures of whole amaranth flour and refined wheat flour. The whole amaranth flours were obtained from the lines called opaca and cristalina and the refined wheat flour from the varieties Fuertemayo F2016 and Urbina S2007. The mixtures with 5, 10 and 15% whole flour of opaca and cristalina amaranth decreased the strength and increased the tenacity of the dough, consequently they decreased the volume of bread and showed crumbs brown in color and with poor texture. On the other hand, mixtures with 25% whole flour of opaca and cristalina amaranth, as well as that of 75% whole flour of cristalina amaranth exceeded the cookie factor of the control variety 100% refined wheat flour, while the rest of the combinations were classified as very good for their cookie factor greater than 4.5. Based on the above, the substitution of whole amaranth flour does not decrease the cookie factor, so it is recommended to use it in mixtures with refined wheat flour, without detracting from the cookie yield, the opposite in the making of bread, where it decreased its volume and therefore the bread yield.